2011
DOI: 10.1371/journal.pone.0017518
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Drug-Refill Is a Useful Early Warning Indicator of Virologic and Immunologic Failure among HIV Patients on First-Line ART in South Africa

Abstract: BackgroundAffordable strategies to prevent treatment failure on first-line regimens among HIV patients are essential for the long-term success of antiretroviral therapy (ART) in sub-Saharan Africa. WHO recommends using routinely collected data such as adherence to drug-refill visits as early warning indicators. We examined the association between adherence to drug-refill visits and long-term virologic and immunologic failure among non-nucleoside reverse transcriptase inhibitor (NNRTI) recipients in South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
81
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 42 publications
(60 reference statements)
14
81
2
Order By: Relevance
“…In this study found that suboptimal drug adherence 9 times more risk of developing treatment failure than optimal adherence. This finding was concordant with study conducted in Kenya [18], South Africa [25] and In Gondar, Ethiopia [26].…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)supporting
confidence: 92%
See 1 more Smart Citation
“…In this study found that suboptimal drug adherence 9 times more risk of developing treatment failure than optimal adherence. This finding was concordant with study conducted in Kenya [18], South Africa [25] and In Gondar, Ethiopia [26].…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)supporting
confidence: 92%
“…In treatment failure, viral load criteria identified failure significantly earlier (median, 47.0 months; p<0.001) than did CD4 count criteria (median, 63.0 months).This study indicated that median time was higher when compared with the study conducted in South Africa 15 months [25], 24 months from Cameroon [24], 24 months from Gondar, Ethiopia [26] and 19.7 months from Addis Ababa, Ethiopia [27].…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)mentioning
confidence: 56%
“…But poor adherence to ART is still seen leading to suboptimal ART regimens, resulting in rapid development of drug resistance. 4,5 Several methods have been developed for measurement of adherence that includes DOT (Directly observed therapy), therapeutic drug monitoring (TDM), medication event monitoring system (MEMS), self-report and Pill counts. 6 In pill count method, adherence is usually calculated by counting the remaining doses of medication and assuming that the remaining pills in excess of what is expected to represent missed doses.…”
Section: Introductionmentioning
confidence: 99%
“…8 In turn, adherence to medication and consistency with clinic visits has been shown to be significantly associated with improved clinical outcomes in patients living with HIV/AIDS in these settings. 8,[13][14][15][16] Consistent clinic attendance to a scheduled ART refill appointment has been suggested as a relatively easy way to identify nonadherent patients on ART over time in resource-poor settings. 13,16,17 In this study, we assessed the incidence of adherence to ART in a cohort of HIV-infected patients in a large urban Tanzanian HIV Care and Treatment program using adherence to clinic ART refill visits as a surrogate measure.…”
Section: Introductionmentioning
confidence: 99%